Multichannel Acquisition and Biosignal Multimodal Processing for Moving Patients: Methodologies for Optimal Design of Wearable Cardiac Monitoring Systems (2016)
Abstract: The study presented in this thesis demonstrates how new approaches for cardiac monitoring can be useful to improve cardiovascular health risk assessment. Throughout six chapters, a set of methodologies for designing wearable monitoring systems (WMS) is presented, evaluated and discussed. Alternative solutions based on new hardware approach, signal processing and optimisation are proposed to the main challenges of noise disturbances, signals characterization and multimodal processing, originated from ambulatory acquisition in daily life scenarios. Chapter 1 provides an introduction of the thesis. It begins with the research problem statement, followed by the justification, the hypothesis to be proved by the results and the objectives of the research. Chapter 2 is a review of the state off the art, organized into three parts: acquisition, signal processing and optimisation of designs. Chapter 3, contributions regarding the acquisition hardware are presented, including new models and techniques to manage aspects of hygiene, electrode-skin contact, and context influence. Also, prototypes using the proposed models are developed and evaluated. After having developed the basic tools for ambulatory data acquisition, Chapter 4, is focused on three novel methods for the processing of ECG signals. Chapter 5, describes a method to optimise the design of these systems for the specific application of cardiac monitoring. Finally, Chapter 6 is a discussion about the research findings regarding the methods used to develop WSM and observations for the validation of the hypothesis.